O „Świętej Wspólnocie”, rewolucji i Antychryście. Religijne poszukiwania inteligencji rosyjskiej na przełomie XIX i XX wieku - Krycka-Michnowska, Iwona (Przegląd Rusycystyczny, 2013)
Iwona Krycka-Michnowska iekrycka@uw.edu.pl О „СВЯТОЙ ОБЩЕСТВЕННОСТИ”, РЕВОЛЮЦИИ И AНТИХРИСТЕ. ИЗ ИСТОРИИ РЕЛИГИОЗНЫХ ИСКАНИЙ РУССКОЙ ИНТЕЛЛИГЕНЦИИ НА РУБЕЖЕ XIX И XX ВВ. Резюме Одними из инициаторов обновления русской религиозной жизни на рубеже веков были Зинаида Гиппиус (1869–1945) и Дмитрий Мережковский (1865–1941), предпри-нявшие попытку создать «святую общественность» как предтечу Bселенской Церкви и организовать Религиозно-философские собрания в Санкт-Петербурге в 1901–1903 гг. Эти мероприятия описала Зинаида Гиппиус в своих дневниках, мемуарах, письмах и эссе, представляющих собой ценный материал по русской культуре и истории. Со-поставление этих текстов позволяет раскрыть эволюцию идейной позиции их автора, его непростое отношение к Богу, религии, власти и государству. THE “HOLY COMMUNITY,” THE REVOLUTION AND THE ANTICHRIST. THE HISTORY OF THE RELIGIOUS QUEST RUSSIAN INTELLIGENTSIA IN THE LATE 19th AND EARLY 20th CENTURIES Summary One of the main initiators of the Russian renewal of religious life in the late nineteenth and early twentieth centuries were Zinaida Hippius (1869–1945) and Dmitry Merezhkovsky. Their most important project was an attempt to create a “holy community” as an origin of the ecumenical Church, and alternative to “historical Churches” and organization of the Religious-Philosophical Meetings (1901–1903) in St. Petersburg. This initiative is descri-bed in Zinaida Hippius’ diaries and memoirs, which is the subject of our reflections in this article. The confrontation of these texts, which are valuable material about Russian culture and history, reveals the evolution of the author’s ideological stance, her complex relationship to God, religion, government and the state.